Effect of a Nursing Comprehensive Skill Training Course (NCST-C) on Nursing Students' Metacognitive Awareness: A Quasi-experimental Study - Shasha Li; Minerva de Ala; Dandan Mao; Afeng Wang; Chongwen Wu (Asian Nursing Research, 2022)
Summary: Purpose: This study explored the effect of a nursing comprehensive skill training course (NCST-C) on the metacognitive awareness of nursing students to provide a scientific foundation for improving metacognitive awareness. Methods: This study used a quasi-experimental two-group matched pretest, post-test, and follow-up test. Ninety-six junior nursing students were recruited using convenience sampling and assigned to two groups by drawing lots with odd and even numbers in a nursing school at Huzhou University. The control group received a traditional skill-training course. The intervention group received NCST-C. Nursing students' metacognitive awareness inventory (MAI) was evaluated at the baseline, 16-week, and 20-week follow-up points. A repeated-measures analysis of variance and a simple effect test was used to compare each outcome measure of the two groups three times. Results: The NCST-C resulted in greater benefits for nursing students' metacognitive awareness as well as various dimensions (knowledge of cognition and regulation of cognition) in the intervention group. Combined with a simple effects test, the MAI and dimension scores of those in the intervention group significantly improved at 16 weeks after the baseline (F = 9.78–44.03; all ps < .01). The sustainable effect of NCST-C lasted 1 month after the intervention (F = 14.24–62.36; ps < .01), reaching statistical significance (p < .05). Conclusions: The NCST-C effectively developed metacognitive awareness among nursing students. Its design provides a new type of experimental course for improving metacognitive awareness. Trial registration: chictr.org.cn: ChiCTR2200057910. First registration date: 1/11/2020.